Expression of embryonic stem cell markers in acute myeloid leukemia. Issue 7 (July 2017) - Picot, Tiphanie; Aanei, Carmen Mariana; Fayard, Amandine; Flandrin-Gresta, Pascale; Tondeur, Sylvie; Gouttenoire, Marina; Tavernier-Tardy, Emmanuelle; Wattel, Eric; Guyotat, Denis; Campos, Lydia
Acute myeloid leukemia is driven by leukemic stem cells which can be identified by cross lineage expression or arrest of differentiation compared to normal hematopoietic stem cells. Self-renewal and lack of differentiation are also features of stem cells and have been associated with the expression of embryonic genes. The aim of our study was to evaluate the expression of embryonic antigens (OCT4, NANOG, SOX2, SSEA1, SSEA3) in hematopoietic stem cell subsets (CD34 + CD38 − and CD34 + CD38 + ) from normal bone marrows and in samples from acute myeloid leukemia patients. We observed an upregulation of the transcription factors OCT4 and SOX2 in leukemic cells as compared to normal cells. Conversely, SSEA1 protein was downregulated in leukemic cells. The expression of OCT4, SOX2, and SSEA3 was higher in CD34 + CD38 − than in CD34 + CD38 + subsets in leukemic cells. There was no correlation with biological characteristics of the leukemia. We evaluated the prognostic value of marker expression in 69 patients who received an intensive treatment. The rate of complete remission was not influenced by the level of expression of markers. Overall survival was significantly better for patients with high SOX2 levels, which was unexpected because of the inverse correlation with favorable genetic subtypes. These results prompt us to evaluate the potential role of these markers in leukemogenesis and to test their relevance for better leukemic stem cell identification.